Dentoalveolar fracture: A complication of extraction of upper left first molar - Tay, Zhuo Wei (Clin Case Rep, 2018)
The current trend of managing maxillary tuberosity fractures is traumatic and results in the loss of bone and teeth. Treatment options that chose to retain the fractured segments and teeth have been perceived to be unfavorable. This case report shows that maxillary tuberosity fractures can be treated conservatively.